Ranitidine, diarrhoea, and lymphocytic colitis. Issue 5 (November 1995) - Beaugerie, L; Patey, N; Brousse, N
Abstract : A 69 year old woman developed chronic diarrhoea while being treated with ranitidine. Sigmoidoscopy was performed after six weeks and showed typical histological features of lymphocytic colitis. Ranitidine was withdrawn and the diarrhoea resolved. Eight months later, a 72 hour oral rechallenge period of ranitidine, was performed immediately preceded (period 1) and followed (period 2) by sigmoidoscopy and biopsy. Diarrhoea recurred during the rechallenge period and resolved again within one day after drug withdrawal. The mean (SEM) intraepithelial lymphocyte count was not significantly different between periods 1 and 2 (11.9 (0.6) and 13.1 (0.4) per 100, respectively). An immunopathological study of 30 serial sections of biopsy specimens was performed for both periods 1 and 2. The expression of HLA-DR by the rectal epithelium was mild or absent in all sections from period 1, and was considerable in 25 of 30 sections from period 2 (p < 10(-9)). It is suggested that the oral intake of ranitidine was responsible for the diarrhoea and induced the immunopathological signs of activation of the rectal mucosal immune system during the rechallenge period.